Evaluation of the sustainability impacts of informal gold recovery from cellular phones - Pesigan, Clarissa M.; Soriano, Virginia Jose (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The current technological innovations call for more electrical and electronics products introduced into the market that have planned obsolescence and disposability leading to the rapid increase of the amount of the e-wastes generated globally. Cellular phones are one of the interesting subjects for study due to its high quantity, high reuse/recovery value and fast replacement frequency. They are also small which makes it easier for them to be stored, forgotten, or eventually thrown with other households wastes, thus, losing the opportunity to recover value from recyclable elements and posing threats to the ecosystem and human health due to its toxic contents. As cited by EMB-DENR in one of their reports, backyard e-waste recyclers abound in the Philippines. This entails both a problem and an opportunity. On one hand, devoid of any business and environmental permits and clearances, their waste could just be thrown anywhere exposing the environment and the people to environmental and health risks. On the other hand, these practices provide economic benefits to the recyclers and can be a secondary source of gold, complement with training. Thus, this study evaluated the impacts of informal gold recovery from cellular phones based on three sustainability pillars consisting of the environmental, economic and social aspects, by comparing it with primary gold production (i.e. small scale production sites) to serve as the baseline to evaluate its desirability. Quantifying these impacts could help the government evaluate the extent of the effects of the informal gold recovery sector in environmental problems and propose a win-win solution to minimize the problems and maximize its socio-economic potential. Results suggest that from the environmental perspective , informal gold recovery contributes largely to toxicity mainly due to the large amount of heavy metals and toxic elements found in the wastewater, like lead, arsenic, cadmium and chromium. Comparing it with other mining sites namely Manabo. Licuan-baay, and Benguet. With Benguet as the best-in-class production registering the lowest environmental burden, informal gold recovery closely follows, entailing minimal environmental impact. However, it registered the lowest economic impact as represented by productivity. This is primarily contributed by labor, but looking at the socio-economic impact, this entails economic benefit to the workers as the fair salary provides them an opportunity their quality of life. Moreso, informal gold recovery has the most benign social impact as evidenced by the low level of risk posed to the health and safety of workers and the community. Overall, it can be concluded that informal gold recovery is desirable from the sustainability standpoint. It is less environmentally benign than most of the small-scale mining activities in the different sites considered and also relatively economically viable and socially acceptable. If all the sustainability issues can be addressed properly, this mode of gold production can be recommended for scaling up, thereby providing employment benefits while providing industries dependent on gold for production with a secondary source of raw materials.
Thesis (M.S. Industrial Engineering)--University of the Philippines Diliman
Keywords: Electronic waste -- Recycling; Gold